2009
DOI: 10.1016/j.otsr.2008.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal landmarks for TKR implantations: Evaluation of their accuracy using EOS imaging acquisition system

Abstract: The lower extremity skeletal landmarks precision relates to the quality of the corresponding 3D reconstructions. Except for tibial rotation, all the translation and rotation parameters were estimated within a mean error margin inferior to 1.2 mm and 1.3 degrees, respectively. Making the reconstruction algorithms more robust would render certain anatomic zones even more precise. Biplanar low-dose EOS X-ray system is a tool of the future to generate 3D knee X-rays that can improve the evaluation and follow-up of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 19 publications
1
32
0
Order By: Relevance
“…Stratified by pincer size, rotation, and tilt, the intermodality ICCs showed excellent reliability between EOS 1 and conventional radiography in morphologic features of the pincer. Our study also is consistent with previous EOS 1 imaging studies, which all showed an image quality of EOS 1 comparable to improved compared with that of conventional radiography [1,6,17,18,20,24,31]. However, we did see relative horizontal widening of the image in EOS 1 with extreme anterior tilt (C 10°) and horizontal narrowing in extreme posterior tilt (C 10°) owing to the decrease or increase in distance between the x-ray beam and the pelvis (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Stratified by pincer size, rotation, and tilt, the intermodality ICCs showed excellent reliability between EOS 1 and conventional radiography in morphologic features of the pincer. Our study also is consistent with previous EOS 1 imaging studies, which all showed an image quality of EOS 1 comparable to improved compared with that of conventional radiography [1,6,17,18,20,24,31]. However, we did see relative horizontal widening of the image in EOS 1 with extreme anterior tilt (C 10°) and horizontal narrowing in extreme posterior tilt (C 10°) owing to the decrease or increase in distance between the x-ray beam and the pelvis (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Some of them were specially designed to obtain precise 3D measurements before surgery [13,30,33]. However, factors related to complexity of these techniques, reproducibility and accessibility could impede their use in daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…Systems that take multiple radiographs of the knee from which a 3D image is created have been developed but are not widely used at present. 18,25 Of these, the sterEOS system (EOS imaging SA, Paris, France) appears to provide a viable alternative to 3D CT reconstruction, with a considerably lower radiation exposure.…”
Section: Alignment and Positioning Of The Componentsmentioning
confidence: 99%